High-performance carbon-coated sodium vanadium fluorophosphate positive electrode material, sodium ion battery as well as preparation method and application of sodium vanadium fluorophosphate positive electrode material and sodium ion battery
By carbon coating on the sodium vanadium fluorophosphate positive electrode material, the problem of its low electronic conductivity is solved, the preparation process is simplified, and the high-performance and low-cost sodium vanadium fluorophosphate positive electrode material is realized, which promotes the development of sodium ion batteries.
Patent Information
- Application Number
- CN202311195840.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
AI Technical Summary
The low electronic conductivity of the existing sodium vanadium fluorophosphate cathode material limits its practical application in sodium ion batteries, and the existing preparation methods are expensive, complex in operation, and difficult to industrialize.
The carbon-coated sodium vanadium fluorophosphate positive electrode material is prepared on a large scale through a simple preparation method, and its electronic conductivity is improved through in-situ coating of carbon and electrochemical performance is improved.
The carbon-coated sodium vanadium fluorophosphate cathode material with high electronic conductivity and excellent electrochemical properties simplifies the preparation process, reduces costs, and promotes its commercial development.
Smart Images

Figure CN119637829A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of sodium ion batteries, and in particular relates to a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material, a sodium ion battery, and a preparation method and application thereof. Background Art
[0002] The higher reserves and more even distribution of sodium in the earth's crust, as well as the similar charge-discharge mechanism of sodium-ion batteries as lithium-ion batteries, create conditions for the manufacture of low-cost sodium-ion batteries. Promoting the development of sodium-ion batteries and achieving a complementary pattern with lithium-ion batteries is of great significance to the development of clean energy. However, the large radius and large mass of sodium ions limit the further development of sodium-ion batteries. In order to increase the energy density of batteries, obtaining suitable positive electrode materials is the key to improving specific capacity.
[0003] At present, the existing cathode materials mainly include polyanionic compounds, layered transition metal oxides, Prussian blue analogs and organic compounds. Among them, sodium vanadium fluorophosphate (Na3V2(PO4)2F3) is a polyanionic compound with a Na superconductor structure and exhibits a high working potential (3.95V vs Na / Na + ), theoretical specific capacity (128 mAh g -1 ) and energy density (507Wh·kg -1 ). Therefore, sodium vanadium fluorophosphate cathode material is widely considered to be the future cathode material for sodium ion batteries. However, the low electronic conductivity caused by its [PO4] tetrahedral unit limits its practical application, so it is still far from the goal of practical application.
[0004] In the prior art, technicians have used methods such as nano-sizing, carbon coating, heterogeneous ion doping, and adjusting crystal facet growth to prepare the corresponding sodium vanadium fluorophosphate positive electrode materials, but these methods are costly, complicated to operate, and difficult to truly industrialize. Therefore, it is urgent to find a low-cost and simple preparation method of high-performance sodium vanadium fluorophosphate positive electrode material and apply it to the preparation of sodium ion batteries. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material, a sodium ion battery, and a preparation method and application thereof. A simple preparation method is used to realize large-scale preparation of carbon-coated sodium vanadium fluorophosphate positive electrode material, and its electronic conductivity is improved by in-situ carbon coating, thereby improving the electrochemical performance and promoting its commercial development.
[0006] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:
[0007] On the one hand, the present application provides a method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material, comprising the following steps:
[0008] (1) heating a mixture containing a sodium source, a vanadium source, a phosphorus source, a fluorine source, a carbon source, and water for 1 h, stirring until a gel is formed, and drying to obtain a precursor;
[0009] (2) ball milling the precursor, and then heating it in an inert gas atmosphere II to obtain the high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material.
[0010] Optionally, the molar ratio of the sodium source, vanadium source, phosphorus source and fluorine source in step (1) is 3 to 3.2:2:2:3;
[0011] The molar numbers of the sodium source, vanadium source, phosphorus source and fluorine source are calculated based on the atomic molar numbers of sodium, vanadium, phosphorus and fluorine therein.
[0012] Optionally, the sodium source in step (1) includes one or more of sodium citrate, sodium carbonate and sodium fluoride.
[0013] Optionally, the vanadium source in step (1) includes one or more of ammonium metavanadate, sodium vanadate, vanadium pentoxide, hydrated vanadium oxalate and vanadium chloride.
[0014] Optionally, the phosphorus source in step (1) includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid.
[0015] Optionally, the fluorine source in step (1) includes one or more of sodium fluoride, ammonium bifluoride and ammonium fluoride.
[0016] Optionally, the carbon source in step (1) includes one or more of sodium citrate, citric acid, glucose and hexadecyltrimethylammonium bromide.
[0017] Optionally, the heating I in step (1) includes a first heating and a second heating;
[0018] The first heating temperature is 60-100° C.;
[0019] The first heating time is 1 to 3 hours;
[0020] The second heating temperature is 100-200°C.
[0021] Optionally, the stirring speed in step (1) is 300 to 1000 rpm.
[0022] Optionally, the drying temperature in step (1) is 100-200°C.
[0023] Optionally, the rotation speed of the ball mill in step (2) is 300-400 rpm.
[0024] Optionally, the inert gas in step (2) includes argon.
[0025] Optionally, the heating II in step (2) is segmented heating;
[0026] The staged heating is firstly heating to 300-400° C., keeping the temperature for 3-5 hours, and then heating to 700-900° C., keeping the temperature for 6-10 hours.
[0027] In a second aspect, the present application provides a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the above preparation method.
[0028] In a third aspect, the present application provides the use of the above-mentioned high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material in the preparation of sodium ion batteries.
[0029] In a fourth aspect, the present application provides a sodium ion battery, which comprises the above-mentioned high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material.
[0030] Compared with the prior art, this application has the following beneficial effects:
[0031] (1) The present application mainly improves the electronic conductivity and electrochemical properties of sodium vanadium fluorophosphate by adjusting the ratio and type of sodium source, vanadium source, phosphorus source and fluorine source, thereby obtaining a carbon-coated sodium vanadium fluorophosphate positive electrode material with high electronic conductivity and excellent electrochemical properties.
[0032] (2) The preparation method provided in the present application is simple, the raw material composition is simple, and the prepared carbon-coated sodium vanadium fluorophosphate has good crystallinity, high working potential, excellent cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope image of the carbon-coated sodium vanadium fluorophosphate prepared in Example 1 of the present application;
[0034] Figure 2 This is the XRD pattern of the carbon-coated sodium vanadium fluorophosphate prepared in Example 1 of the present application;
[0035] Figure 3 This is a rate performance diagram of the carbon-coated sodium vanadium fluorophosphate half-cell prepared in Example 1 of the present application;
[0036] Figure 4 This is a cycle performance diagram of the carbon-coated sodium vanadium fluorophosphate half-cell prepared in Example 1 of the present application at a current density of 5C;
[0037] Figure 5This is a scanning electron microscope image of the carbon-coated sodium vanadium fluorophosphate prepared in Example 2 of the present application;
[0038] Figure 6 This is the XRD pattern of the carbon-coated sodium vanadium fluorophosphate prepared in Example 2 of the present application;
[0039] Figure 7 This is a rate performance diagram of the carbon-coated sodium vanadium fluorophosphate half-cell prepared in Example 2 of the present application;
[0040] Figure 8 This is a cycle performance diagram of the carbon-coated sodium vanadium fluorophosphate half-cell prepared in Example 2 of the present application at a current density of 5C;
[0041] Fig. 9 This is a scanning electron microscope image of the carbon-coated sodium vanadium fluorophosphate prepared in Example 3 of the present application;
[0042] Fig.10 This is the XRD pattern of the carbon-coated sodium vanadium fluorophosphate prepared in Example 3 of the present application;
[0043] Fig.11 This is a rate performance diagram of the carbon-coated sodium vanadium fluorophosphate half-cell prepared in Example 3 of the present application;
[0044] Fig.12 This is a cycling performance diagram of the carbon-coated sodium vanadium fluorophosphate half-cell prepared in Example 3 of the present application at a current density of 5C. DETAILED DESCRIPTION
[0045] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0046] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0047] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0048] The following examples use a scanning electron microscope (SEM, JSM-7900F) to analyze the sample morphology; an X-ray diffractometer (XRD, SmartLab) to analyze the sample composition; and a LAND CT3001A battery system (Wuhan Landian Electronics Co., Ltd.) to test the electrochemical performance. The room temperature in the following examples refers to "25°C".
[0049] Example 1
[0050] 2.941g sodium citrate, 2.3396g ammonium metavanadate, 2.3g ammonium dihydrogen phosphate, and 0.8856g ammonium bifluoride with an atomic substance ratio of 3:2:2:3 of sodium, vanadium, phosphorus, and fluorine are used as raw materials, among which sodium citrate also serves as a carbon source. First, add ammonium metavanadate to 40mL deionized water and heat and stir at 80℃ for 1h. Then add ammonium dihydrogen phosphate, sodium citrate, and ammonium bifluoride, stir at 80℃ for 2h, and stir at 350rpm. Then heat to 120℃, stir at 350rpm, and stir until the solution becomes a gel. Then move into an oven and dry at 120℃ overnight. Ball mill the dried precursor. Then use argon atmosphere for heat treatment, and use segmented heating to treat the sample. First heat to 350℃, keep warm for 4h, then heat to 800℃, and keep warm for 8h. Finally, a carbon-coated sodium vanadium fluorophosphate product is obtained.
[0051] Example 2
[0052] 2.941g sodium citrate, 2.3396g ammonium metavanadate, 2.3g ammonium dihydrogen phosphate, and 1.1112g ammonium fluoride with an atomic substance ratio of 3:2:2:3 of sodium, vanadium, phosphorus, and fluorine are used as raw materials, among which sodium citrate also serves as a carbon source. First, add ammonium metavanadate to 40mL deionized water and heat and stir at 80℃ for 1h. Then add ammonium dihydrogen phosphate, sodium citrate and ammonium fluoride, stir at 80℃ for 2h, and stir at 350rpm. Then heat to 120℃, stir at 350rpm, and stir until the solution becomes a gel. Then move into an oven and dry at 120℃ overnight. Ball mill the dried precursor. Then use argon atmosphere for heat treatment, and use segmented heating to treat the sample. First heat to 350℃, keep warm for 4h, then heat to 800℃, and keep warm for 8h. Finally, a carbon-coated sodium vanadium fluorophosphate product is obtained.
[0053] Example 3
[0054] 2.3396g of ammonium metavanadate, 2.3g of ammonium dihydrogen phosphate, and 1.25g of sodium fluoride with an atomic substance ratio of 3:2:2:3 of sodium, vanadium, phosphorus, and fluorine were used as raw materials, and 2.1014g of citric acid was used as an additional carbon source, in which sodium fluoride served as both a sodium source and a fluorine source. First, add ammonium metavanadate to 40mL of deionized water and heat and stir at 80°C for 1h. Then add ammonium dihydrogen phosphate, citric acid, and sodium fluoride, stir at 80°C for 2h, and stir at 350rpm. Then heat to 120°C, stir at 350rpm, and stir until the solution becomes a gel. Then move into an oven and dry at 120°C overnight. Ball mill the dried precursor. Then use an argon atmosphere for heat treatment, and use segmented heating to treat the sample. First heat to 350°C, keep warm for 4h, then heat to 800°C, and keep warm for 8h. Finally, a carbon-coated sodium vanadium fluorophosphate product is obtained.
[0055] Experimental Example 1
[0056] Taking Example 1 as an example, the prepared carbon-coated sodium vanadium fluorophosphate product was subjected to SEM analysis, XRD analysis and electrochemical performance test:
[0057] The results of SEM and XRD analysis are as follows Figure 1 and Figure 2 As shown. Figure 1 It can be seen from the scanning electron microscope (SEM) that the carbon-coated sodium vanadium fluorophosphate prepared in Example 1 has a block structure. Figure 2 It can be seen from the X-ray diffraction pattern (XRD) that the carbon-coated sodium vanadium fluorophosphate prepared in Example 1 has good crystallinity, and the diffraction peaks of the sample can well correspond to the standard JCPDS card (PDF#89-8485), showing a tetrahedral symmetric structure with a space group of P42 / mnm.
[0058] The carbon-coated sodium vanadium fluorophosphate prepared in Example 1 was mixed with a conductive agent (carbon black) and a binder (PVDF) in a mass ratio of 8:1:1, and coated on a current collector to form a positive electrode sheet. The cut positive electrode sheet was combined with a sodium metal negative electrode to form a half-cell, and the electrochemical performance of the prepared carbon-coated sodium vanadium fluorophosphate electrode material was tested. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3 The rate test shows that the electrode material can provide reversible capacities of 108, 105, 98, 85, 71 and 50 mAh / g at 0.1, 0.2, 0.5, 1, 2 and 5C. Figure 4 It can be seen that at a current density of 5C, the carbon-coated sodium vanadium fluorophosphate electrode prepared in Example 1 still has a capacity of 69.8 mAh / g after 500 cycles, and the capacity retention rate is 75.6%, which has excellent cycle stability.
[0059] Experimental Example 2
[0060] Taking Example 2 as an example, the prepared carbon-coated sodium vanadium fluorophosphate product was subjected to SEM analysis, XRD analysis and electrochemical performance test:
[0061] The results of SEM and XRD analysis are as follows Figure 5 and Figure 6 As shown. Figure 5 It can be seen from the scanning electron microscope (SEM) that the carbon-coated sodium vanadium fluorophosphate prepared in Example 2 has a block structure. Figure 6 It can be seen from the X-ray diffraction pattern (XRD) that the carbon-coated sodium vanadium fluorophosphate prepared in Example 2 has good crystallinity, and the diffraction peaks of the sample can well correspond to the standard JCPDS card (PDF#89-8485), showing a tetrahedral symmetric structure with a space group of P42 / mnm.
[0062] The carbon-coated sodium vanadium fluorophosphate prepared in Example 2 was mixed with a conductive agent (carbon black) and a binder (PVDF) in a mass ratio of 8:1:1, and coated on a current collector to form a positive electrode sheet. The cut positive electrode sheet was combined with a sodium metal negative electrode to form a half-cell, and the electrochemical performance of the prepared carbon-coated sodium vanadium fluorophosphate electrode material was tested. The results are as follows: Figure 7 and Figure 8 As shown. Figure 7 The rate test shows that the electrode material can provide reversible capacities of 97, 90, 80, 71, 62 and 54 mAh / g at 0.1, 0.2, 0.5, 1, 2 and 5C. Figure 8 It can be seen that at a current density of 5C, the carbon-coated sodium vanadium fluorophosphate electrode prepared in Example 2 still has a capacity of 59.1 mAh / g after 500 cycles, and the capacity retention rate is 65.7%, which has excellent cycle stability.
[0063] Experimental Example 3
[0064] Taking Example 3 as an example, the prepared carbon-coated sodium vanadium fluorophosphate product was subjected to SEM analysis, XRD analysis and electrochemical performance test:
[0065] The results of SEM and XRD analysis are as follows Fig. 9 and Fig.10 As shown. Fig. 9 It can be seen from the scanning electron microscope (SEM) that the carbon-coated sodium vanadium fluorophosphate prepared in Example 3 has a block structure. Fig.10It can be seen from the X-ray diffraction pattern (XRD) that the carbon-coated sodium vanadium fluorophosphate prepared in Example 3 has good crystallinity, and the diffraction peaks of the sample can well correspond to the standard JCPDS card (PDF#89-8485), showing a tetrahedral symmetric structure with a space group of P42 / mnm.
[0066] The carbon-coated sodium vanadium fluorophosphate prepared in Example 3 was mixed with a conductive agent (carbon black) and a binder (PVDF) in a mass ratio of 8:1:1, and coated on a current collector to form a positive electrode sheet. The cut positive electrode sheet was combined with a sodium metal negative electrode to form a half-cell, and the electrochemical performance of the prepared carbon-coated sodium vanadium fluorophosphate electrode material was tested. The results are as follows: Fig.11 and Fig.12 As shown. Fig.11 The rate test shows that the electrode material can provide reversible capacities of 96, 78, 62, 53, 46 and 41 mAh / g at 0.1, 0.2, 0.5, 1, 2 and 5C. Fig.12 It can be seen that at a current density of 5C, the carbon-coated sodium vanadium fluorophosphate electrode prepared in Example 3 still has a capacity of 50.7 mAh / g after 500 cycles, and the capacity retention rate is 73.7%, which has excellent cycle stability.
[0067] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material, characterized in that: The steps include: (1) heating a mixture containing a sodium source, a vanadium source, a phosphorus source, a fluorine source, a carbon source, and water for 1 h, stirring until a gel is formed, and drying to obtain a precursor; (2) ball milling the precursor, and then heating it in an inert gas atmosphere II to obtain the high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material.
2. The method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the sodium source, vanadium source, phosphorus source and fluorine source in step (1) is 3 to 3.2:2:2:3; The molar numbers of the sodium source, vanadium source, phosphorus source and fluorine source are calculated based on the atomic molar numbers of sodium, vanadium, phosphorus and fluorine therein.
3. The method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: The sodium source in step (1) includes one or more of sodium citrate, sodium carbonate and sodium fluoride; Preferably, the vanadium source in step (1) comprises one or more of ammonium metavanadate, sodium vanadate, vanadium pentoxide, hydrated vanadium oxalate and vanadium chloride; Preferably, the phosphorus source in step (1) comprises one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid; Preferably, the fluorine source in step (1) comprises one or more of sodium fluoride, ammonium bifluoride and ammonium fluoride; Preferably, the carbon source in step (1) comprises one or more of sodium citrate, citric acid, glucose and hexadecyltrimethylammonium bromide.
4. The method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: The heating I in step (1) includes a first heating and a second heating; The first heating temperature is 60-100° C.; The first heating time is 1 to 3 hours; The second heating temperature is 100-200°C; Preferably, the stirring speed in step (1) is 300 to 1000 rpm.
5. The method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: The drying temperature in step (1) is 100-200°C.
6. The method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: The rotation speed of the ball mill in step (2) is 300-400 rpm; Preferably, the inert gas in step (2) comprises argon.
7. The method for preparing a high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: The heating II in step (2) is staged heating; The staged heating is firstly heating to 300-400° C., keeping the temperature for 3-5 hours, and then heating to 700-900° C., keeping the temperature for 6-10 hours.
8. The high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 8 in the preparation of sodium ion batteries.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the high-performance carbon-coated sodium vanadium fluorophosphate positive electrode material according to claim 8.
Citation Information
Cited By
W-doped modified sodium vanadium fluorophosphate positive electrode material and preparation method thereof
CN121044562A